The Influence of Women in the Board of Commissioners, CFO, and the Audit Committee on Earnings Quality - Septian B. Kristanto, Fanny A. Setiawan, Herni Kurniawati, (Jurnal Akuntansi, 2020)
This research tries to prove whether in Indonesia the presence of women in companies is needed to hold positions of the Board of Commissioners, Chief Financial Officer (CFO) and the Audit Committee in order to generate quality profits to attract investors. This research is quantitative using panel data regression to test whether or not there is an effect of the presence of female gender on the positions of the Board of Commissioners, CFO, and the Audit Committee on earnings quality. The research sample is a manufacturing company in the 2013-2017 period using secondary data. The results of the research are (1) the presence of women holding positions in the Board of Commissioners causes a decline in the quality of earnings; (2) The presence of women in CFO can reduce the quality of earnings; and (3) The presence of women in the Audit Committee improves the quality of earnings.